2015
DOI: 10.1073/pnas.1508074112
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analyses of melanoma reveal complex patterns of metastatic dissemination

Abstract: Melanoma is difficult to treat once it becomes metastatic. However, the precise ancestral relationship between primary tumors and their metastases is not well understood. We performed whole-exome sequencing of primary melanomas and multiple matched metastases from eight patients to elucidate their phylogenetic relationships. In six of eight patients, we found that genetically distinct cell populations in the primary tumor metastasized in parallel to different anatomic sites, rather than sequentially from one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
142
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(157 citation statements)
references
References 38 publications
9
142
4
2
Order By: Relevance
“…Advances in genetics have helped unravel the genetic complexity of melanoma as well as intratumoral heterogeneity (11,35). Our data show that differences in TCRs resident within these lesions are greater than the genetic differences between individual metastases, and therefore, these TCR differences are likely not explained simply by differences in candidate neoepitopes in these lesions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Advances in genetics have helped unravel the genetic complexity of melanoma as well as intratumoral heterogeneity (11,35). Our data show that differences in TCRs resident within these lesions are greater than the genetic differences between individual metastases, and therefore, these TCR differences are likely not explained simply by differences in candidate neoepitopes in these lesions.…”
Section: Discussionmentioning
confidence: 74%
“…Genomic studies of tumor cells have demonstrated a complex and heterogeneous landscape with a potential intratumoral heterogeneity effect on clinical outcome (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individual metastases have been shown to be founded by multiple cell populations in the primary melanoma (11) highlighting the complexity of metastatic progression. Although few treatments have been available in metastatic melanoma, the recent development of inhibitors targeting BRAF and MEK changed the clinical outcome of patients with metastatic disease (12).…”
Section: Introductionmentioning
confidence: 99%
“…26 Advances in genetics have helped reveal the genetic complexity of melanoma and intratumoral heterogeneity. 27,28 In addition, TCR sequencing has shown that differences in T cell receptor residents within these lesions are greater than the genetic differences between individual metastases. 29 This discovery stimulates us to investigate whether the spatial discordance of PD-L1 and TILs in the primary lesion microenvironment has a different meaning.…”
mentioning
confidence: 99%